Living Teologi Tradisi Tolak Bala Bepapas pada Masyarakat Desa Parit Setia Kecamatan Jawai Kabupaten Sambas Kalimantan Barat - Revi Madriani (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study examines Islam that lives in the Parit Setia community. In the Parit Setia community there is a tradition tolak bala Bepapas. The purpose of this research is to answer the problems that are the subject of discussion: 1) Definition of the tradition tolak bala Bepapas; 2) Understanding the community's theology of the tradition tolak bala Bepapas; and 3) The values contained in the tradition tolak bala Bepapas. This research is a field research, with a phenomenological approach, qualitative methods, and living theology as a knife of analysis. The findings in this research show that: First, historically the tradition tolak bala Bepapas is a tradition that resulted from a mixture of culture and religion. Tradition is carried out as an effort to avoid all forms of danger, which is symbolized through leaves and is led by a traditional leader (pak Labbai). Second, this tradition has long been rooted so that it is considered sacred. Even though there are differences of opinion in responding to it, this tradition still exists today as a cultural identity of society. Third, the determination of religious values contained in this tradition is based on the principles of tawhid, which substantially have values for relating to nature, maintaining friendship, asking for salvation and as a form of gratitude to Allah SWT. Observing all the findings in the field, it is not an exaggeration to conclude that this tradition is a living Islam (living Islamic theology) in the Parit Setia community.